Quantitative flow cytometric analysis of opsonophagocytosis and killing of nonencapsulated Haemophilus influenzae by human polymorphonuclear leukocytes. - Vogel, L (1994)
Since nonencapsulated Haemophilus influenzae persists in the lower respiratory tracts of patients with chronic bronchitis despite the presence of specific antibodies, complement, and polymorphonuclear leukocytes (PMNs), opsonophagocytosis of H. influenzae was analyzed. Nonencapsulated H. influenzae isolated from the sputa of chronic bronchitis patients was labeled with fluorescein isothiocyanate and incubated with human PMNs in the presence of complement and antibodies for 30 min at 37 degrees C. Candida albicans was added to each sample as an internal standard, and the reduction of the number of bacteria was determined by flow cytometry. Fluorescence quenching with ethidium bromide was used to discriminate between intracellular and extracellular bacteria. Opsonophagocytosis of viable H. influenzae d1 was 17% +/- 29% in the presence of complement and human pooled sera containing high titers of strain-specific antibodies. Opsonophagocytosis of six other H. influenzae strains was also poor. Under the same conditions, opsonophagocytosis of Staphylococcus aureus was 90% +/- 5%, and opsonophagocytosis of C. albicans was 55% +/- 23%. About half of the number of H. influenzae bacteria associated with PMNs was internalized. Opsonophagocytosis of heat-killed H. influenzae d1 (41% +/- 20%) was higher than that of viable bacteria of the same strain (P < 0.05). This result suggests that the accessibility of epitopes on H. influenzae for opsonizing antibodies is better on killed than on viable bacteria. We conclude that viable nonencapsulated H. influenzae is poorly opsonophagocytized in the presence of strain-specific antibodies and complement.